1981
DOI: 10.1086/159338
|View full text |Cite
|
Sign up to set email alerts
|

Solar luminosity variation. III - Calcium K variation from solar minimum to maximum in cycle 21

Abstract: Measurement of the full disk Ca n H and K profiles has now been completed from minimum to maximum in the current solar cycle 21. The central intensity of the K line increases by 30% on the average, but a peak change of-1-40% was recorded near the maximum of solar activity in late 1979. The 1 A K index shows a corresponding but smaller increase of 18%. These changes in the Sun viewed as a star appear to be directly attributable to the occurrence of solar plages on the visible solar hemisphere. Similar measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 0 publications
5
77
0
Order By: Relevance
“…This conclusion is consistent with the data published by Jensen and Orrall ( 1963) in which 18% of their slit sample has no chromospheric emission peaks in the K line profile. Skumanich et al (1984) showed that the Skumanich et al (1975) distribution and its calibration are in good agreement with White and Livingston (1981) K radiance measurements of the quiet, i.e., nonplage, areas near disk center, i.e., the equatorial region of the star, as well as with the WL K irradiance measurements at solar minimum when magnetic areas have their smallest contribution to the K emission for the contemporary Sun. We note that the polar magnetic flux is also a minimum at the time of minimum solar activity (Murray 1992) and must be similarly distributed as the Skumanich et al (1975) equatorial distribution, as we have assumed.…”
Section: Mapping Of the Radiance Distribution For Solar Magetic Strucsupporting
confidence: 61%
See 1 more Smart Citation
“…This conclusion is consistent with the data published by Jensen and Orrall ( 1963) in which 18% of their slit sample has no chromospheric emission peaks in the K line profile. Skumanich et al (1984) showed that the Skumanich et al (1975) distribution and its calibration are in good agreement with White and Livingston (1981) K radiance measurements of the quiet, i.e., nonplage, areas near disk center, i.e., the equatorial region of the star, as well as with the WL K irradiance measurements at solar minimum when magnetic areas have their smallest contribution to the K emission for the contemporary Sun. We note that the polar magnetic flux is also a minimum at the time of minimum solar activity (Murray 1992) and must be similarly distributed as the Skumanich et al (1975) equatorial distribution, as we have assumed.…”
Section: Mapping Of the Radiance Distribution For Solar Magetic Strucsupporting
confidence: 61%
“…Since Wilson's 1967 and1969 measurements were made before we began the direct solar measurements at Kitt Peak and Sac Peak, we use the 10.7 cm radio flux as a surrogate for the index at the times assigned by Wilson to his four solar values. See White and Livingston (1981) for an example of the Ca il K and 10.7 cm flux solar cycle correlation in cycle 21. We smoothed the radio flux record with a 12-month running mean and determined the radio flux at the four times given by Wilson (1978Wilson ( ), i.e., 1967Wilson ( .3, 1969Wilson ( .5, 1975Wilson ( .5, 1976.7.…”
Section: Ca II K Irradiance Scalesmentioning
confidence: 99%
“…Direct, longterm H & K observations of the Sun began at the National Solar Observatory (NSO) in 1974 using the McMath solar telescope at Kitt Peak (White and Livingston, 1978), and in 1976 at Sacramento Peak (Keil and Worden, 1984). By the peak of solar cycle 21, it was apparent that the "HK index," the total emission in a 1Å rectangle centered on the line cores, closely tracked the sunspot number, plage index, and 10.7 cm flux (White and Livingston, 1981). The NSO workers also monitored a number of photospheric features (e.g., C i 5380 and several iron lines) to study the relationship between chromospheric activity, photospheric structure, and solar and stellar luminosity (Livingston et al, 1977;Livingston and Holweger, 1982;White et al, 1987); see also Section 4.6.…”
Section: Long-term Observations Of Ca II H and Kmentioning
confidence: 99%
“…Ground-based observations of chromospheric and photospheric proxies since 1974 from the National Solar Observatory (NSO) at Kitt Peak (KP) and Sacramento Peak (SP) are reported in a number of papers (e.g., White and Livingston, 1981;Livingston and Holweger, 1982;Keil and Worden, 1984;Worden et al, 1998, and references therein), and Livingston et al (2006) have provided a thorough summary of these synoptic observations from 1974 through 2006. Figure 14 shows representative long-term solar observations from the NSO program (from Livingston et al, 2006, Figure 18).…”
Section: Sun-as-a-star Observationsmentioning
confidence: 99%
“…(1) No cyclic variations: Caii K emission in solar quiet regions (White & Livingston 1981); X-ray bright points (Hara & Nakakubo 2003); magnetic flux of networks (Labonte & Howard 1982); flux spectrum and total flux of network elements with flux 2.0 × 10 19 Mx (Hagenaar et al 2003); Stokes Q I profile (Trujillo Bueno et al 2004). (2) Anti-correlation of small-scale fields with sunspot cycle: number of network bright points in very quiet regions (Muller & Roudier 1984, 1994; Heii 10830Ådark points in the higher chromosphere (Harvey 1985); coronal X-ray bright points (Davis et al 1977;Davis 1983;Golub et al 1979;Sattarov et al 2002); weak changes of emergence frequency of ephemeral regions with flux less than (3-5)×10 19 Mx (Hagenaar et al 2003).…”
Section: Introductionmentioning
confidence: 99%